Fraud Pentagon and Fraudulent Financial Reporting in Jakarta Islamic Index - Surepno, Surepno; Cahya, Bayu Tri; Andriani, Asih; Marpaung, Muslim (Ekonomi Syariah IAIN Kudus, 2021)
This study aims to examine pentagon fraud with five elements that can influence the occurrence of fraudulent financial reporting on the Jakarta Islamic Index. fraud pentagon has five elements there is pressure, opportunity, rationalization, competence (competence/ability), and arrogance. This research is a quantitative study using logistic regression analysis methods with SPSS tools. The results showed that fraud pentagon with five elements can influence the occurrence of fraudulent financial reporting in companies incorporated in the Jakarta Islamic Index. But among the five elements are pressure, opportunity, rationalization, competence (competency /ability), the element of arrogance does not have a significant effect on the occurrence of fraudulent financial reporting.